Critérios De Manejo Na Irrigação Do Feijoeiro Em Solo De Textura Arenosa - de Brito, Ramilos Rodrigues [UNESP]; Grassi Filho, Hélio [UNESP]; Saad, João Carlos Cury [UNESP]; Ribeiro, Valdenir Queiroz; Oliveira, Simone Raquel Mendes (My University, 2015)
One of the most important contributors to the success of irrigated agriculture is an efficient management of water applied by irrigation. Several methodologies and tools exist in the market for that purpose, however, monitoring the soil water level using tensiometers has proved to be effective. This study evaluated two methods of irrigation management, one based on soil water tension and the other on depletion of available water. The objective was to evaluatewhich one would promote higher grain yield. Treatments consisted of five levels of tension: (- 30, - 40, - 50, - 60 and - 70 kPa) and five levels of depletion (30, 40, 50, 60 e 70% AD) with four replicates. The experimental design was randomized blocks. The experiment was conducted in a greenhouse at the Soil Sciences/Natural Resources Department (UNESP/FCA), Botucatu, São Paulo state. The following parameters were evaluated: Number of pods per plant (NPP, g), production of pods per plant (PPP, g), pod length (PL, cm), number of grains per pod (NGP), grain weight per pod (GWP,g), weight of 100 grains (W100G,g) and grain production (GP, g plant-1). No significant differences were found between the irrigation methods, however, the highest bean grain yield was observed for tension of – 30 kPa, which resulted in 12.10g plant-1 and 11.04 g plant-1 for 40% AD.
Management criteria for bean irrigation in sandy texture soil
Keywords: Depletion; Phaseolus vulgaris L; Tension; Yield components